Investor intention in equity crowdfunding: Does trust matter? - Mohammed Alharbey; Stefan van Hemmen (Journal of Risk and Financial Management, 2021)
Equity crowdfunding (ECF) is becoming a convenient alternative instrument for investing in entrepreneurs' projects in many countries. The purpose of this study was to investigate the factors that affect the investor's intentions toward ECF platforms in Saudi Arabia, where they have not been introduced until very recently. This context offers a unique opportunity to test the role of investors' perceived trust in the context of ECF. The proposed framework builds on two critical layers: (1) trust in the platform (intermediary) and (2) trust in the fundraiser. Structured equation modelling was applied to examine the factors that affect investors' trust and intentions. The framework was analysed using survey data from 216 users of Manafa, one of the largest ECF platforms in Saudi Arabia. Our findings showed that both fundraiser and platform trust have a significant effect on the investor's intentions. In particular, trust in the platform substantially impacts the fundraiser's trust, showing the importance of the fundraiser's reliance on trusted institutions. On the other hand, to build investors' trust, fundraisers must deliver high-quality information for their projects.
Keywords: 330; equity crowdfunding; intention; structural equation modelling; trust